2020
DOI: 10.1017/s0959270920000520
|View full text |Cite
|
Sign up to set email alerts
|

Predation of nesting Thick-billed Parrots Rhychopsitta pachyrhyncha by bobcats in northwestern Mexico

Abstract: Summary We report on what appear to be increasing predation events on nesting Thick-billed Parrots Rhychopsitta pachyrhyncha. Thick-billed Parrots are classified as ‘Endangered’ and their seasonal breeding range is restricted to increasingly fragmented and degraded high elevation mixed conifer forest habitat within the Sierra Madre Occidental region of north-western Mexico. Predation of established breeding pairs has recently contributed to the ongoing decline of Thick-billed Parrot populations by removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Availability of nesting cavities in mature trees and snags in the Sierra Madre Occidental has dramatically decreased in recent decades due to destructive clear-cutting and high-intensity timbering of remnant old-growth primary forests. Installation of artificial nest boxes at parrot breeding sites has helped improve nesting success and reduced predation risk (Sheppard et al 2021), although this solution is labor and resource intensive and difficult to sufficiently scale. As of 2023, only 19.6 % of the total thick-billed parrot nesting home range area, 8.5 % of the total overwintering home range area, and 6.4 % of the total area of migratory stopover sites that we calculated are covered by formal regulatory protections, such as a reserve or natural protected area designation (Appendix 4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Availability of nesting cavities in mature trees and snags in the Sierra Madre Occidental has dramatically decreased in recent decades due to destructive clear-cutting and high-intensity timbering of remnant old-growth primary forests. Installation of artificial nest boxes at parrot breeding sites has helped improve nesting success and reduced predation risk (Sheppard et al 2021), although this solution is labor and resource intensive and difficult to sufficiently scale. As of 2023, only 19.6 % of the total thick-billed parrot nesting home range area, 8.5 % of the total overwintering home range area, and 6.4 % of the total area of migratory stopover sites that we calculated are covered by formal regulatory protections, such as a reserve or natural protected area designation (Appendix 4.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of thick-billed parrot populations conducted over the past 25 years within their remaining breeding sites show a decline of 20 – 30 %. The most recent surveys indicate there may be fewer than 2000 individual birds extant (Sheppard et al 2021), although this number is dubitable due to the irregularity of survey intensity. This precipitous drop in thick-billed parrot populations has been linked to the decline in suitable nesting resources (Monterrubio et al 2002, Monterrubio-Rico and Enkerlin-Hoeflich 2004), as well as a trend observed in recent years of increasing predation events on nesting thick-billed parrots and their chicks (Sheppard et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Threats faced by the thick-billed parrot include habitat loss due to logging operations throughout its range as well as historical pet trade capture and shooting [37][38][39]. A recent study discovered evidence of increased rates of predation by bobcats and recommended increased antipredation methods at nesting sites [40]. Studies have suggested that reduction of logging and favorable ecological conditions in the thick-billed parrot habitat range are key to its recovery [41].…”
Section: Introductionmentioning
confidence: 99%